2017
DOI: 10.1186/s12864-017-4255-8
|View full text |Cite
|
Sign up to set email alerts
|

XTHs from Fragaria vesca: genomic structure and transcriptomic analysis in ripening fruit and other tissues

Abstract: Background Fragaria vesca or ‘woodland strawberry’ has emerged as an attractive model for the study of ripening of non-climacteric fruit. It has several advantages, such as its small genome and its diploidy. The recent availability of the complete sequence of its genome opens the possibility for further analysis and its use as a reference species. Fruit softening is a physiological event and involves many biochemical changes that take place at the final stages of fruit development; among them, the remodeling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…The first glutamate residue (E) acts as catalytic nucleophile which initiates the enzymatic reaction and the second one as a base to activate the substrate. All members of HvXTH family, except HvXTH15 (ancestral group), had a conserved N -glycosylation site (marked with asterisks), which is proximal to the catalytic residues as reported in Fragaria vesca [12]. The N -glycosylation site domain (NxT/S/Y) is thought to play a role in protein stability.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The first glutamate residue (E) acts as catalytic nucleophile which initiates the enzymatic reaction and the second one as a base to activate the substrate. All members of HvXTH family, except HvXTH15 (ancestral group), had a conserved N -glycosylation site (marked with asterisks), which is proximal to the catalytic residues as reported in Fragaria vesca [12]. The N -glycosylation site domain (NxT/S/Y) is thought to play a role in protein stability.…”
Section: Resultsmentioning
confidence: 95%
“…Detailed three-dimensional structures of Tm-NXG1 and Tm-NXG2 revealed the major structural features of the active site regulating relative rates of hydrolysis to transglycosylation in GH16 xyloglucan-active enzymes transformation, suggesting that XTH genes evolved to have a role in cell wall remodeling [11]. A study of XTHs in Fragaria vesca also suggested a similar classification of XTH genes and revealed differing expression levels of XTHs during different developmental stages of fruit ripening and in different tissues [12].…”
Section: Introductionmentioning
confidence: 99%
“…The XTHs can catalyze endolytic cleavage of xyloglucan polymers, thereby promoting fruit softening [86]. The XTH genes also participate in the degradation of cell walls [91] and are involved in fruit softening [92,93]. Yun et al [94] confirm that an XTH gene can promote the ripening of banana fruit by the degradation of hemicelluloses.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, mRNA for xyloglucan endotransglucosylase was highly abundant in MT fruit in the early developmental stages and xyloglucan endotransglucosylase was predicted as the target of miR9480a. A discrete group of FvXTHs increased their expression during softening of wild strawberry fruit, which was required for cell wall remodeling in fruit softening [42]. Expansin-A1 was up-regulated in MT fruit from S2 to S4, it is the target of miR8175 (Table 2).…”
Section: Xyloglucan Endotransglucosylase (Xth) Plays a Dual Role In Integration Of Newly Secreted Xyloglucan Chains Into An Existing Wallmentioning
confidence: 99%